Next‐generation sequencing for patients with non‐obstructive azoospermia: implications for significant roles of monogenic/oligogenic mutations. (July 2017) - Nakamura, S.; Miyado, M.; Saito, K.; Katsumi, M.; Nakamura, A.; Kobori, Y.; Tanaka, Y.; Ishikawa, H.; Yoshida, A.; Okada, H.; Hata, K.; Nakabayashi, K.; et al.
Summary: Azoospermia affects up to 1% of adult men. Non‐obstructive azoospermia is a multifactorial disorder whose molecular basis remains largely unknown. To date, mutations in several genes and multiple submicroscopic copy‐number variations (CNVs) have been identified in patients with non‐obstructive azoospermia. The aim of this study was to clarify the contribution of nucleotide substitutions in known causative genes and submicroscopic CNVs in the genome to the development of non‐obstructive azoospermia. To this end, we conducted sequence analysis of 25 known disease‐associated genes using next‐generation sequencing and genome‐wide copy‐number analysis using array‐based comparative genomic hybridization. We studied 40 Japanese patients with idiopathic non‐obstructive azoospermia. Functional significance of molecular alterations was assessed by in silico analyses. As a result, we identified four putative pathogenic mutations, four rare polymorphisms possibly associated with disease risk, and four probable neutral variants in 10 patients. These sequence alterations included a heterozygous splice site mutation in SOHLH1 and a hemizygous missense substitution in TEX11, which have been reported as causes of non‐obstructive azoospermia. Copy‐number analysis detected five X chromosomal or autosomal CNVs of unknown clinical significance, in addition to one known pathogenic Y chromosomal microduplication. Five patients carried multiple molecular alterations. The results indicate that monogenic and oligogenic mutations, including those in SOHLH1 and TEX11, account for more than 10% of cases of idiopathic non‐obstructive azoospermia. Furthermore, this study suggests possible contributions of substitutions in various genes as well as submicroscopic CNVs on the X chromosome and autosomes to non‐obstructive azoospermia, which require further validation.